Gerontoxanthone I and Macluraxanthone Induce Mitophagy and Attenuate Ischemia/Reperfusion Injury - Xiang, Qian; Wu, Man; Zhang, Li; Fu, Wenwei; Yang, Jinling; Zhang, Baojun; Zheng, Zhaoqing; Zhang, Hong; Lao, Yuanzhi; Xu, Hongxi (Frontiers in Pharmacology, 2020)
Mitophagy is a crucial process in controlling mitochondrial biogenesis. Balancing mitophagy and mitochondrial functions is required for maintaining cellular homeostasis. In this study, we found that Gerontoxanthone I (GeX1) and Macluraxanthone (McX), xanthone derivatives isolated from Garcinia bracteata C. Y. Wu ex Y. H. Li, induced Parkin puncta accumulation and promoted mitophagy. GeX1 and McX treatment induced the degradation of mitophagy-related proteins such as Tom20 and Tim23. GeX1 and McX directly stabilized PTEN-induced putative kinase 1 (PINK1) on the outer membrane of the mitochondria, and then recruited Parkin to mitochondria. This significantly induced phosphorylation and ubiquitination of Parkin, suggesting that GeX1 and McX mediate mitophagy through the PINK1-Parkin pathway. Transfecting ParkinS65A or pretreated MG132 abolished the induction effects of GeX1 and McX on mitophagy. Furthermore, GeX1 and McX treatment decreased cell death and the level of ROS in an ischemia/reperfusion (IR) injury model in H9c2 cells compared to a control group. Taken together, our data suggested that GeX1 and McX induce PINK1-Parkin–mediated mitophagy and attenuate myocardial IR injury in vitro.